A novel route to prepare N-graphene/SnO2 composite as a high-performance anode for lithium batteries. Issue 30 (17th July 2018) - Liang, Kuang; Zhao, Zhi-Wei; Zhou, Xiao; Xu, An-Wu
Abstract : In this study, we report a simple method to prepare nitrogen-doped graphene, with which a nitrogen-doped graphene/SnO2 composite was successfully fabricated and employed as a lithium battery anode. Abstract : In this study, we report a simple method to prepare nitrogen-doped graphene, with which a nitrogen-doped graphene/SnO2 composite was successfully fabricated and employed as a lithium battery anode. Electrochemical test results indicated that the as-prepared nitrogen-doped graphene/SnO2 electrode possesses high reversible capacity and outstanding charging and discharging capabilities, which would make it possible to meet the requirements for portable electronic devices in the future. These super electrochemical properties could benefit from the synergistic effect of SnO2 nanoparticles that contribute to the high capacity and nitrogen-doped graphene that could enhance the electroconductivity. Moreover, the graphene nanosheet provides a large specific surface area for SnO2 nanoparticles to anchor on, which could efficiently overcome the structure destruction of SnO2 -based electrodes during continuous charging and discharging tests. This concept can offer a general approach toward designing anode materials with better performance.